ASSESSMENT OF THE QUALITY OF ENRICHED YEAST-FREE BREAD FROM DIFFERENT TYPES OF FLOUR - RATSUK, MARIIA; YUROVA, TATYANA; SARIBYEKOVA, YULIYA; CHYKHUN, OLHA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Today, nutrition is an important factor that determines the state of human health. It is thanks to the right diet that the human body resists the harmful effects of the environment, which affects life expectancy and even the emotional state. The world is facing the issue of the relevance of producing products characterized by high nutritional value and high consumer properties. Bread is accessible to all segments of the population and is one of the most consumed products. There is a growing interest in yeast-free bread, which is widely considered to be healthier and more nutritious, usually contains more vitamins and minerals, and has a lower glycemic index, i.e. less impact on blood sugar levels, making it more beneficial for diabetics The possibility of making yeast-free bread using different types of flour: rye, whole wheat, and first-grade wheat was investigated. The organoleptic characteristics of the prepared bread products were determined. It was found that all the prepared bread samples comply with the regulatory documentation in terms of surface condition, consistency, smell, and taste. Thus, based on the results of the organoleptic tests, all types of flour used in the study can be used for the preparation of yeast-free bread. To increase the nutritional value of bread products, it is proposed to add pumpkin meal, a natural product of plant origin containing more than 50 different biologically active components: a significant amount of proteins, essential amino acids, vitamins, minerals, and dietary fiber, to the recipe of unleavened bread made from different types of flour, which can improve the quality and nutritional value of bread. It has been shown that the addition of meal in the amount of 5% provides excellent organoleptic characteristics for the resulting bread products.